The role of Halal Certification in increasing sales of Micro, Small, and Medium Enterprise Products in Belitung Regency - Tibroni, Ahmad (EJESH: Journal of Islamic Economics and Social, 2024)
The halal aspect has become a global trend and a need for people in the world. Indonesia is a potential halal market in the future. Indonesia has the resources or capabilities, capacity and potential to become a world halal center. So the halal certification system becomes a necessity which is expected to protect both safety and halal aspects. This research uses a qualitative method approach. The results of this research show that halal certification has a role in gaining consumer trust, increasing sales and expanding marketing. Apart from that, halal certification is a strategic step to retain consumers for companies, increase competitiveness and provide added value to a product. MSME players in Belitung Regency stated that having Halal Certification can be an added value and can increase sales and income after being certified halal. Indirectly, Halal Certification has an influence and provides added value to every product sold by MSMEs in Belitung Regency so that consumers do not hesitate to consume food sold in the area.